Sensaciones recuperadas para “En el huerto” de Primeras hojas. Una conversación del martes 31 de mayo de 1977 - González Martel, Juan Manuel (Revista de Filología Románica, 2008)
This work, conceived as a tribute to Alonso Zamora Vicente, recalls several scenes from its author’s College years, shared with the unforgettable Maestro.